Pemanfaatan Zat Pengatur Tumbuh (ZPT) Alami Berbasis Fermentasi Mikroba untuk Meningkatkan Pertumbuhan dan Kualitas Bibit Tanaman dalam Polibag pada Kelompok Tani Desa Reuleut Timu - Almuna Ramadhani; Mira Humaira; Zurrahmi Wirda; Dian Arlianty; Nanda Fadila; Novita Pramahsari Putri (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
This Community Service Program (PkM) aims to enhance farmers’ knowledge and skills in utilizing natural Plant Growth Regulators (PGR) based on microbial fermentation for seedling production in polybags. The partners involved were farmer groups in Reuleut Timu Village, who still face limitations in applying organic-based seedling technologies. The implementation method used a participatory approach consisting of socialization, field demonstration (demonstration plot), and hands-on practice in producing and applying natural PGR. Evaluation was conducted through observation, discussions, and pre-test and post-test assessments to measure knowledge improvement. The results show an increase in farmers’ understanding of natural PGR and microbial fermentation, improved skills in producing and applying PGR independently, and better seedling growth quality indicated by increased vigor, plant height, and leaf number. The program also promotes the optimization of local resources and strengthens farmer-group-based seedling systems. Therefore, the participatory approach is effective in supporting the adoption of sustainable agricultural technologies at the village level.